A framework to improve training and development of workers' technical skills: Effects on operational performance during company relocation - Pinto, Luís (2020)
A case study is presented in a food and beverage company, during the transfer of a production plant location. To address the problems of loss of industrial technicians and closing emerging gaps in knowledge of tasks' execution to be performed by new technicians, the company has implemented mitigation actions: work characterization, the creation of standard procedures, and the implementation of operational control routines, among others. The process of technical skills development for the production center was systematized by a framework developed for this purpose. The use of this framework, combined with a specifically designed training program, allowed for improvements in technicians' proficiency in performing operational tasks that have a direct influence on the process performance, as evidenced by the improvement of Overall Equipment Effectiveness. This framework could be adaptable to other manufacturing companies to improve Training and Development skills of their workers, aiming to create and transfer of intraorganizational knowledge.